Lung alveolar tissue destruction and protein citrullination in diesel exhaust‐exposed mouse lungs. Issue 2 (2nd April 2019) - Kulvinskiene, Ieva; Raudoniute, Jovile; Bagdonas, Edvardas; Ciuzas, Darius; Poliakovaite, Karina; Stasiulaitiene, Inga; Zabulyte, Danguole; Bironaite, Daiva; Rimantas Venskutonis, Petras; Martuzevicius, Dainius; Aldonyte, Ruta
Abstract: Humanity faces an increasing impact of air pollution worldwide, including threats to human health. Air pollutants prompt and promote chronic inflammation, tumourigenesis, autoimmune and other destructive processes in the human body. Post‐translational modification of proteins, for example citrullination, results from damaging attacks of pollutants, including smoking, air pollution and others, rendering host tissues immunogenic. Citrullinated proteins and citrullinating enzymes, deiminases, are more prevalent in patients with COPD and correlate with ongoing inflammation and oxidative stress. In this study, we installed an in‐house–designed diesel exhaust delivery and cannabidiol vaporization system where mice were exposed to relevant, urban traffic–related levels of diesel exhaust for 14 days and assessed integrity of alveolar tissue, gene expression shifts and changes in protein content in the lungs and other tissues of exposed mice. Systemic presence of modified proteins was also tested. The protective effect of phytocannabinoids was investigated as well. Data obtained in our study show subacute effects of diesel exhaust on mouse lung integrity and protein content. Emphysematous changes are documented in exposed mouse lungs. In parallel, increased levels of citrulline were detected in the alveolar lung tissue and peripheral blood of exposed mice. Pre‐treatment with vaporized cannabidiol ameliorated some damaging effects. Results reported hereby provide new insights into subacute lung tissue changes that follow diesel exhaust exposure and suggest possible dietary and/or other therapeutic interventions for maintaining lung health and healthy ageing.